Flow Curves and Fluid Loss of Water-Based Drilling Fluids (Annual Transactions of the Nordic Rheology Society, 2025)
A drilling fluid must fulfill numerous functions during well drilling, ranging from particle transport, lubrication, to wall stabilization.  In that aim, the composition is carefully chosen by the drilling engineer for each well section according to the required properties such as density, rheological properties, chemical stability, and fluid loss. In particular, fluid loss refers to the penetration of the liquid from the drilling fluid into the rock formation. It must be controlled and preferably avoided as it may reduce the permeability of the formation and change the fluid properties due to the depletion of the liquid. Fluids with low fluid loss can form an impermeable filter cake at the rock surface, i.e., a layer of accumulated particles on the wall of the well.As interest in CO2 storage has increased in the last decade, the need to design drilling fluids for CO2 well drilling has arisen. Lots of knowledge is inherited from oil & gas wells, and still, CO2 wells pose new challenges. These wells should not be optimized for production (receiving fluids from the formation into the well), but for injection (injecting CO2 from the well into the rock formation). Here, we present an experimental study aiming to optimize drilling fluids' rheological properties and fluid loss for CO2 wells. Flow curves are measured using a Couette cell in an Anton Paar rheometer. Fluid loss and filter cake formation are evaluated with a filter press. We investigate the effect of the fluid components on the flow curve, the fluid loss, and the filter cake mass.